Learning React - Krikheli, Lasha (Packt Publishing, 2019)
"This course will cover all of the React.js basics such as its API, which will help you create elements and components; the virtual DOM and the JSX syntax extension; using state; working with browser events; and component lifecycle methods. You will build an application from scratch throughout the course and use the knowledge you've gained in a practical way. You will also learn to update various elements of a site or application seamlessly without delay, without disrupting the rest of the display or requiring the user to refresh. Also, get introduced to the new concept of hooks. Finally, you will work with a server API to persist data using local storage. (Note that we use Node.js 10.13.0 for this course, which will run successfully with the React features we cover.). By the end of the course, you will be fully capable of using ReactJ.js tools to build several UI elements, making them reactive to user input, and extending your knowledge of DOM manipulation to customize your own UIs in the future."--Resource description page